Ordinary Smooth Topological Spaces - Lim, Pyung-Ki; Ryoo, Byeong-Guk; Hur, Kul (INTERNATIONAL JOURNAL of FUZZY LOGIC and INTELLIGENT SYSTEMS, 2012)
In this paper, we introduce the concept of ordinary smooth topology on a set X by considering the gradation of openness of ordinary subsets of X. And we obtain the result [Corollary 2.13] : An ordinary smooth topology is fully determined its decomposition in classical topologies. Also we introduce the notion of ordinary smooth [resp. strong and weak] continuity and study some its properties. Also we introduce the concepts of a base and a subbase in an ordinary smooth topological space and study their properties. Finally, we investigate some properties of an ordinary smooth subspace.